2009
DOI: 10.1136/bjo.2008.149047
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and glaucoma

Abstract: Although intraocular pressure (IOP) is considered the main risk factor for the development of glaucoma and the only parameter subject to treatment, there is sufficient evidence to suggest that glaucoma may continue to progress despite lowering patients' IOP to targeted levels. Several studies have implicated vascular risk factors in the pathogenesis of glaucoma. Among them, blood pressure (BP) and ocular perfusion pressure have become increasingly important. Although clinicians cannot currently visualise ocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
64
0
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 94 publications
1
64
0
18
Order By: Relevance
“…[33][34][35] A complete description of the theory how low OPP may be involved in glaucoma pathogenesis has been summarized in recent reviews. 36,37 With regard to the present data, it is of interest that ONHBF appears to have relatively little regulatory capacity when IOP is increased.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] A complete description of the theory how low OPP may be involved in glaucoma pathogenesis has been summarized in recent reviews. 36,37 With regard to the present data, it is of interest that ONHBF appears to have relatively little regulatory capacity when IOP is increased.…”
Section: Discussionmentioning
confidence: 99%
“…4 Since then, the impact of BP on glaucoma has received greater attention as more evidence has mounted. [5][6][7] Despite the increasing evidence of an association between BP and glaucoma, the exact relationship is complex. In this matter, epidemiological and case-control studies have shown diverse results, and some studies have presented evidence of a correlation between high BP and glaucoma, [5][6][7][8][9][10][11] whereas other studies have linked glaucoma and low-tension glaucoma with low BP.…”
mentioning
confidence: 99%
“…[5][6][7] Despite the increasing evidence of an association between BP and glaucoma, the exact relationship is complex. In this matter, epidemiological and case-control studies have shown diverse results, and some studies have presented evidence of a correlation between high BP and glaucoma, [5][6][7][8][9][10][11] whereas other studies have linked glaucoma and low-tension glaucoma with low BP.12-17 The controversies have been discussed and related to the complexity of BP not only influencing IOP and ocular perfusion pressure, but also increasing the risk of compromised peripheral vascular capacity and a dysfunctional autoregulation. 5,[17][18][19] Recognized high BP is treated with many different antihypertensive medications, and growing evidence acknowledges that such treatment is associated with glaucoma.…”
mentioning
confidence: 99%
“…Nowadays, the concept of OPP and its identification of this as an important risk factor for the development and progression of glaucoma have brought together the vascular and mechanical components of glaucoma. Costa et al, believe that it is the balance between IOP and arterial pressure, influenced by the autoregulatory capacity of the eye that determine whether an individual will develop optic disc damage or not (26) . Some authors suggested that glaucoma patients with an exaggerated nocturnal reduction in systemic arterial pressure have an altered OPP outside the period of arterial pressure reduction, which is possibly related to a general vascular dysregulation (27) .…”
Section: Discussionmentioning
confidence: 99%